Photographs of the Brazilian Civil-Military Dictatorship in history textbooks (Revista Tempo e Argumento, 2016)
AbstractThe objective of this article is to analyze the photographs of the Dictatorship present in textbooks that were circulated in Brazil from 1990 to 2015, from the visual culture’s point of view. Taking into consideration that the history textbook is a cultural product, endowed with complexity, we seek to understand its role as creator of cognitive and memory processes. Therefore, we searched ten textbooks edited during this period (and some reissued around that time), three of which are used in this article. Some changes in the use and choice of images were observed, such as the presence of portraits of military presidents, very present in the books edited in the 1990s, and opposition movements against the regime, which finally graced the pages of books around the 2000s. The survey and cataloging of these images may generate, not only categories for analysis, but new understandings about the changes in the way we perceive Brazilian’s Military Dictatorship, from its inception to the present time. Keywords: History teaching; Textbooks; Visual culture; Photography. Original title: Fotografias da Ditadura Civil-Militar brasileira em livros didáticos de história.